OmniSCOPE: Composing Universal Therapies - de Sá, M.; Carriço, L. (Methods of Information in Medicine, 2010)
Objectives: This paper presents Omni SCOPE, an environment for the development of mobile pervasive therapy artifacts. OmniSCOPE builds on SCOPE, a tool for the support of mobile psychotherapy. It aims at providing therapists with means to adjust and compose new therapeutic artifacts to suit their patients’ needs and new therapeutic approaches.Methods: Given the positive results that emerged through the development and utilization of SCOPE, a previous single therapy version of Omni SCOPE, extensions were developed in order to enhance the artifacts, the data collection by patients and its consequent analysis by therapists. These extend the usage possibilities to new situations and therapies also targeting a wider range of users and were developed following a user-centered design approach.Results: As results, we detail the extensions and how they support new activities and therapies illustrated by two case studies in which they are being currently evaluated. Initial results from the involved therapists’ assessment and future trends and directions are also discussed.Conclusions: The features and accessible artifacts that can be composed with Omni-SCOPE have provided therapists with the possibility to enhance their therapy procedures and to reach a wider audience of patients even while out of the office. Additionally, the data gathering options that can be included within the therapeutic artifacts provide much more detail which can clearly facilitate diagnosis and posterior therapy adjustments.
Keywords: Mobile devices; paper-based artifacts; personalized therapy